2011
DOI: 10.1007/s11427-011-4227-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adipogenic differentiation by myostatin is alleviated by arginine supplementation in porcine-muscle-derived mesenchymal stem cells

Abstract: Porcine mesenchymal stem cells in postnatal muscle have been demonstrated to differentiate into adipocytes. This increases adipocyte number and lipid accumulation, and is thought to be the origin of intramuscular fat. In this study, the effects of myostatin and arginine on adipogenic differentiation in mesenchymal stem cells derived from porcine muscle (pMDSCs) were investigated in vitro. Intracellular triglyceride levels were reduced by exogenous myostatin and increased by arginine supplementation or myostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…In the present study, we found that myostatin notably suppressed the expression of the lipid synthesis enzymes Gpdh, Dgat, and Acs1, whereas it promoted the expression of the lipolytic enzyme Cpt1 in fully differentiated 3T3-L1 adipocytes, which indicates that myostatin decreased the intracellular lipid contents by inhibiting lipogenesis and promoting lipolysis. Similar results were obtained in porcine muscle-derived mesenchymal stem cells, which indicated that myostatin inhibited adipogenesis by suppressing the expression of lipid synthesis enzymes (Lei et al 2011). Although myostatin also reduced the expression of the lipolysis enzymes Atgl and Hsl, the total effect of myostatin was a decrease in the lipid accumulation in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, we found that myostatin notably suppressed the expression of the lipid synthesis enzymes Gpdh, Dgat, and Acs1, whereas it promoted the expression of the lipolytic enzyme Cpt1 in fully differentiated 3T3-L1 adipocytes, which indicates that myostatin decreased the intracellular lipid contents by inhibiting lipogenesis and promoting lipolysis. Similar results were obtained in porcine muscle-derived mesenchymal stem cells, which indicated that myostatin inhibited adipogenesis by suppressing the expression of lipid synthesis enzymes (Lei et al 2011). Although myostatin also reduced the expression of the lipolysis enzymes Atgl and Hsl, the total effect of myostatin was a decrease in the lipid accumulation in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 79%
“…At the forefront of treatment options are a family of stem cells, known as mesenchymal stem cells (MSCs), which hold the potential for differentiation into multiple lineages, such as bone, fat, cartilage, tendon and ligament, muscle, and marrow stroma [10,11]. Since the beginning of this field of research, MSCs have been isolated from a variety of sources, including bone marrow, adipose, periosteum, muscle, perichondrium, and synovium [12,13,14,15,16,17,18]. Along with their multipotent capabilities, MSCs also display an amazing ability to self-replicate [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first comprehensive study, in our knowledge, which reports detailed characterization and comparative analysis of a broad panel of porcine integumentary and connective tissue-derived mesenchymal stromal cells. Indeed, the bulk of literature on pMSCs and their preclinical uses in the porcine model are restricted to bone marrow and adipose-derived cells [ 28 – 32 ], with very few reports on the isolation of multipotent pMSCs from porcine skeletal muscle [ 33 35 ], dermis [ 36 , 37 ], and periodontal ligament [ 38 ]. While several reports used decellularized porcine tendon as a biological scaffold to seed human tissue-derived stromal cells [ 39 , 40 ], there exist limited reports on the isolation and characterization of pMSCs derived from porcine tendon tissues.…”
Section: Discussionmentioning
confidence: 99%